4 Manganese enhanced T1 mapping of calcium homeostasis in acute myocardial infarction. (March 2019) - Jasmin, NH; Zaw-Thin, M; Lythgoe, MF; Davidson, S; Stuckey, DJ
Abstract : Introduction: Manganese is a calcium analogue and potent T1-contrast agent for MRI that enters cardiomyocytes through active calcium channels, thus reducing T1 in viable myocardium. 1 We hypothesized that T1-mapping-MRI could measure Mn levels in the myocardium acutely after myocardial infarction (MI) allowing quantification of intracellular Ca response to ischemic injury. Methods: Mice received intraperitoneal injections of 0.10 mmol/kg MnCl2 40 min before MI. T1-mapping-MRI was performed at 1, 2 and 3 hours and 2 days after MI. R1 values (1/T1=the relaxivity of the tissue) were analysed from the area-at-risk of infarction segments (AAR-MI, n=12) and viable segments (Viable-MI, n=12) of infarcted hearts, and naïve control heart (Viable-Naïve, n=12). Imaging was performed using a 9.4T Agilent MRI system and a multi inversion time Look-Locker sequence in the short-axis orientation (TE/TR=3.04/1.11 ms, 18 inversion times at consecutive R waves, 10 0 excitation pulse, slice thickness=1.0 mm, FOV=25.6 × 25.6 mm, matrix size=128 × 128) as described. 2 Results: As soon as 1 hour after MI, R1 values increased in Viable-MI tissue compared with AAR-MI (p<0.0001) and naïve controls. R1 values continued to rise in the Viable-MI at 2 and 3 hours (p=0.02, p=0.01. Figure 1 and 2 ). When the same animals were imaged 2 days post-MI, R1 values were still significantly higher in the Viable-MI tissue compared with AAR-MI tissue (p=0.03). However, Viable-MI tissue had similar R1 to naïve hearts, while R1 in the infarcted AAR-MI was lower than of the naïve myocardium (p=0.03. Figure 1 and 2 ). Discussion: Acutely after ischemic injury a large increase in R1 (reflecting increased Mn 2+ uptake) occurred in Viable-MI myocytes, likely due to elevated catecholamine levels acutely post-MI; increased cardiac work and thus increased Ca 2+ /Mn 2+ uptake. By 2 days the catecholamine storm has passed and R1 levels in the surviving myocardium normalise, while Mn uptake in the dead infarct region was reduced due to lack of functional myocytes. Conclusions: T1-Mapping Manganese-enhanced-MRI offers a valuable in vivo tool for optimisation of the many emerging pharmacological and biological interventions which aim to modulate Ca 2+ homeostasis acuity after MI. References: . Waghorn B, Edwards T, Yang Y, Chuang K-H, Yanasak N, Hu TC-C. Monitoring dynamic alterations in calcium homeostasis by T1-weighted and T1-mapping cardiac manganese-enhanced MRI in a murine myocardial infarction model. NMR in Biomedicine2008;1102–1111. . Stuckey DJ, McSweeney SJ, Thin MZ, Habib J, Price AN, Fiedler LR, … Schneider MD. T1 mapping detects pharmacological retardation of diffuse cardiac fibrosis in mouse pressure-overload hypertrophy. Circulation: Cardiovascular Imaging2014;7:240–249.